Coronary computed tomographic angiography studies: A brief review in analysis, interpretation, and reporting - Teuku Yusrizal; Ivana Purnama Dewi; Rosi Amrilla Fagi (National Scientific Medical Center, 2021)
Coronary computed tomographic angiography (CTA) is a non-invasive procedure that makes it very convenient to imagine the anatomical ability to remove coronary artery disease in patients with chest pain in a population at low to moderate risk. For plaque identification and physiological assessment, coronary CTA may be used, facilitating thorough diagnostic and prognostic assessment of primary prevention in patients. Overall plaque load is assessed by the coronary CTA, plaque subtypes are distinguished and high-risk plaque is identified. The purpose of this article is to review existing applications and practices related to the use of automatic techniques in coronary CTA analysis and interpretation.